2003
DOI: 10.1128/jcm.41.5.1912-1918.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control for β-Lactam Susceptibility Testing with a Well-Defined Collection of Enterobacteriaceae and Pseudomonas aeruginosa Strains in Spain

Abstract: Eighteen Enterobacteriaceae and Pseudomonas aeruginosa strains, 16 of them with well-defined ␤-lactam re sistance mechanisms, were sent to 52 Spanish microbiology laboratories. Interpretative categories for 8 extended-spectrum ␤-lactams were collected. Participating laboratories used their own routine susceptibility testing procedures (88% automatic systems, 10% disk diffusion, and 2% agar dilution). Control results were established by two independent reference laboratories by applying the NCCLS microdilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…This is in contrast with what was reported by Steward et al (29), who observed a high rate of MEs when using other automated systems and suggested laboratories should consider a second independent antimicrobial susceptibility testing method to validate carbapenem intermediateresistant results. On the other hand, our results are in accordance with those reported by R. Cantón et al (4), U. Eigner et al (9), and P. Giakkoupi et al (14). On this matter, Pitout et al have recently recommended that all imipenem-nonsusceptible P. aeruginosa isolates be routinely screened for metallo-␤-lactamase production using the EDTA disk screening test and that confirmation by PCR be performed at a regional reference laboratory (25).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in contrast with what was reported by Steward et al (29), who observed a high rate of MEs when using other automated systems and suggested laboratories should consider a second independent antimicrobial susceptibility testing method to validate carbapenem intermediateresistant results. On the other hand, our results are in accordance with those reported by R. Cantón et al (4), U. Eigner et al (9), and P. Giakkoupi et al (14). On this matter, Pitout et al have recently recommended that all imipenem-nonsusceptible P. aeruginosa isolates be routinely screened for metallo-␤-lactamase production using the EDTA disk screening test and that confirmation by PCR be performed at a regional reference laboratory (25).…”
Section: Discussionsupporting
confidence: 82%
“…The level of performance with the ␤-lactams was a little lower, but comparable to those reported for other commercial methods (4,6,7,8,9,16,18,25,29,31). Within the class, the Phoenix system showed excellent performance for the carbapenems, with no VMEs, no MEs, and very few mEs, ranging from 0.5 to 5.2%.…”
Section: Discussionmentioning
confidence: 54%
“…Surprisingly, the complex mutant phenotype (CM type) was only suspected in a strain carrying natural CTX-M-14 (CCSRC10) in an OmpF Ϫ background. Previously, CLSI or national breakpoints (19) were followed in Spain, but currently, the EUCAST criteria are increasingly being introduced (25% in our study compared with 14% in a recent published study [29] and 0% in previous ones [30,31]). Globally, the error rates were slightly higher (but not significant) in centers using the CLSI criteria (11.8%) than in centers following the EUCAST criteria (10.3%), except for the case of VMEs (3.0% of discrepancies when using EUCAST criteria compared to 0.7% in centers that used CLSI criteria).…”
Section: Discussionmentioning
confidence: 60%
“…In 21 instances where the co-amoxiclav genotypic prediction disagreed with the BD Phoenix results (all involving genotypically susceptible isolates that were resistant by BD Phoenix), all isolates were susceptible according to gradient diffusion, suggesting that in 15% of tests automated phenotyping was overcalling resistance. Problems with the correct assessment of susceptibility by phenotyping for β-lactam/β-lactamase inhibitor combinations have been observed previously, 34 particularly in the context of complex β-lactamase genotypes, 35 which were disproportionately represented in our dataset.…”
Section: Discussionmentioning
confidence: 88%